Community-acquired bacteraemia by Klebsiella pneumoniae producing KPC-3 and resistant to ceftazidime/avibactam. (September 2022) - Machuca, Isabel; Guzmán-Puche, Julia; Pérez-Nadales, E; Gracia-Ahufinger, I; Mendez, A; Cano, A; Castón, JJ; Domínguez, A; Torre-Cisneros, J; Martínez-Martínez, L
ABSTRACT: Objectives: To describe the clinical and microbiological features of a case of community-acquired infection by KPC-producing K. pneumoniae (KPCKP) resistant to ceftazidime/avibactam (CAZ-AVI). Methods: Identification of microorganisms was performed with MALDI Biotyper CA System (BrukerDaltonics, Madrid, Spain). Antimicrobial susceptibility testing was performed using Sensitre EURGNCOL panels (Thermo Fisher Scientific, Madrid, Spain) and gradient strips (Etest, bioMérieux, Madrid, Spain) in the case of CAZ-AVI, using EUCAST breakpoints for interpretation. Whole genome sequencing of blood culture and rectal swab isolates was performed using the Illumina NovaSeq 6000 sequencing system, with 2 × 150-bp paired-end reads (Illumina, Inc.). Results: Blood culture and rectal swab KPCKP isolates were resistant to carbapenems and to CAZ-AVI. The blood culture isolate showed susceptibility to trimethoprim-sulfamethoxazole (TMP-SMX), but the rectal swab culture isolate was resistant to this antibiotic. Both isolates belonged to clonal lineage ST512, harboured a single copy of blaKPC-3 gene, and showed 16 single nucleotide polymorphisms (SNP) between them and 38 SNPs with regard to the first KPC-3 producing K. pneumoniae isolated in our hospital in an initial outbreak in 2012. Genome-wide resistome analysis revealed the presence of a IncFIB(K) plasmid harbouring sul 1 and dfrA 12 genes only in the rectal swab culture isolate, which may explain its resistance to TMP-SMX. Conclusions: Resistance to ceftazidime-avibactam is an emerging nosocomial problem. This case shows that CAZ-AVI-resistant KPCKP strains may disseminate into the community and cause serious infections.